Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Discover comprehensive answers to your questions from knowledgeable professionals on our user-friendly platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Certainly! Let's start with an initial quadratic equation and simplify it step-by-step to demonstrate how it reduces to the form [tex]\(7x^2 - 25x - 300 = 0\)[/tex].
Assume we start with the equation:
[tex]\[14x^2 - 50x - 600 = 0.\][/tex]
We need to simplify this equation. One way to simplify it is by dividing each term by 2. Let's proceed with this step-by-step:
1. Initial Equation:
[tex]\[14x^2 - 50x - 600 = 0.\][/tex]
2. Division by 2:
We divide every term in the equation by 2. The process is as follows:
[tex]\[ \frac{14x^2}{2} - \frac{50x}{2} - \frac{600}{2} = \frac{0}{2} \][/tex]
3. Simplifying Each Term:
[tex]\[ \frac{14x^2}{2} = 7x^2 \][/tex]
[tex]\[ \frac{50x}{2} = 25x \][/tex]
[tex]\[ \frac{600}{2} = 300 \][/tex]
[tex]\[ \frac{0}{2} = 0 \][/tex]
4. Putting It All Together:
Substitute these simplified terms back into the equation:
[tex]\[ 7x^2 - 25x - 300 = 0 \][/tex]
Hence, the original quadratic equation [tex]\(14x^2 - 50x - 600 = 0\)[/tex] simplifies to:
[tex]\[7x^2 - 25x - 300 = 0.\][/tex]
Therefore, we've shown that the equation simplifies to [tex]\(7x^2 - 25x - 300 = 0\)[/tex].
Assume we start with the equation:
[tex]\[14x^2 - 50x - 600 = 0.\][/tex]
We need to simplify this equation. One way to simplify it is by dividing each term by 2. Let's proceed with this step-by-step:
1. Initial Equation:
[tex]\[14x^2 - 50x - 600 = 0.\][/tex]
2. Division by 2:
We divide every term in the equation by 2. The process is as follows:
[tex]\[ \frac{14x^2}{2} - \frac{50x}{2} - \frac{600}{2} = \frac{0}{2} \][/tex]
3. Simplifying Each Term:
[tex]\[ \frac{14x^2}{2} = 7x^2 \][/tex]
[tex]\[ \frac{50x}{2} = 25x \][/tex]
[tex]\[ \frac{600}{2} = 300 \][/tex]
[tex]\[ \frac{0}{2} = 0 \][/tex]
4. Putting It All Together:
Substitute these simplified terms back into the equation:
[tex]\[ 7x^2 - 25x - 300 = 0 \][/tex]
Hence, the original quadratic equation [tex]\(14x^2 - 50x - 600 = 0\)[/tex] simplifies to:
[tex]\[7x^2 - 25x - 300 = 0.\][/tex]
Therefore, we've shown that the equation simplifies to [tex]\(7x^2 - 25x - 300 = 0\)[/tex].
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.